Peningkatan Pembelajaran Tematik Terpadu Menggunakan Model Prolem Based Learning di Sekolah Dasar - Saputra, Febrino Rahmat; Yunisrul, Yunisrul (Universitas Negeri Padang, 2021)
The research is aimed to describe the improvement of the students learning outcomes in learning the integrated thematic subjects by using the Problem Based Learning model (PBL). The classroom action reseby using both qualitative and quantitative approaches. This research was con-ducted in the first semester of academic years 2018/2019. The subjects of the research were teacher and 9 students of the school. The data were collected by using observation, test, and non test. This re-search was conducted through a set of activities such as planning, implementing, observing, and re-flection. The results of the research shows that the lesson plan increased from 85,23% (good) in cycle I to 97,73% (very good) in cycle II. The teacher’s teaching aspect increased from 82,82% (good) in cycle I to 96,88% (very good) in cycle II. Meanwhile, the students learning aspect also increase from 81,25% (good) in cycle I to 96,88% (very good) in cycle II. The students learning iutcome increased from 73,22 in cycle I to 86,55 in cycle II. Thus, the use of Problem Based Learning model improves students learning outcomes in learning the integrated thematic subjects at elementary school.